PENGARUH KUALITAS HOME CARE SEBAGAI SALAH SATU BENTUK PENDAMPINGAN PELAYANAN KESEHATAN - Yuliawan, Anton; Herbasuki, Herbasuki; Asmara, Ika Nugraha Cahayaning (Jurnal Keperawatan GSH, 2023)
ABSTRACTTitle : The Effect of Home Care Quality as a Form of Health Service Assistance in the Work Area of the Sibela Mojosongo Health Center at Surakarta. Research design: the research design uses an analytic survey approach. Research method : Descriptive . Crosssectional with the type of research: quantitative research to explain the effect of the quality of Home  Care services consisting of: reliability, responsiveness, empathy, assurance, and physical appearance on  patient satisfaction and trust in the working area of the Sibela Mojosongo Health Center, Surakarta. Research results: Quality of Home Care Services affects Patient Satisfaction (significance 0.008 < 0.05),  Quality of Home Care Services influences Patient Trust (significance 0.001 < 0.05), Patient Satisfaction influences Patient Trust (significance 0.000 < 0.05). Conclusion: There is a significant relationship between service quality and patient satisfaction and patient  satisfaction is related to the level of patient trust in health care products (home care). For this reason, it is  necessary to improve the quality of home care services. ABSTRAKJudul : Pengaruh Kualitas Home Care Sebagai Salah Satu Bentuk Pendampingan Pelayanan KesehatanDi Wilayah Kerja Puskesmas Sibela Mojosongo Surakarta. Desain penelitian: desain penelitian menggunakan pendekatan survey analitik. Metode penelitian : Deskriptive Crossectional. Dengan jenis penelitian : penelitian kuantitatif untuk menjelaskan pengaruh kualitas pelayanan Home Care yang terdiri dari: kehandalan, ketanggapan, empati, jaminan, dan tampilan fisik terhadap kepuasan dan kepercayaan pasien di wilayah Kerja Puskesmas Sibela Mojosongo Surakarta. Hasil penelitian : Kualitas Layanan Home Care berpengaruh terhadap Kepuasan Pasien (signifikasi 0,008 < 0,05), Kualitas Layanan Home Care berpengaruh terhadap Kepercayaan Pasien (signifikasi0,001 < 0,05), Kepuasan Pasien berpengaruh terhadap Kepercayaan Pasien (signifikasi 0,000 < 0,05). Kesimpulan : Ada pengaruh yang bermakna antara kulaitas pelayanan dengan kepuasan pasien dan  kepuasan pasien berhubungan dengan tingkat kepercayaan pasien terhadap produk layanan kesehatan  (home care). Untuk itu perlu adanya peningkatan mutu layanan home care.